2014
DOI: 10.15407/fz59.06.025
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Intermittent Hypoxia Trainings on the Functional Status of Corticoliberin- And Betaendorphin-Synthesizing Neurons of the Paraventricular Nucleus Hypothalamus in Rats

Abstract: Вплив переривчастих гіпоксичних тренувань на функціональний стан кортиколіберин і βендорфінсинтезуючих нейронів паравентрикулярного ядра гіпоталамуса щурів В експерименті на щурах показано, що гіпоксичні тренування призводять до посилення імунореактивності до кортиколіберину і β-ендорфіну та збільшення їх вмісту у паравентрикулярному ядрі гіпоталамуса. При цьому показник відношення площі імунореактивного матеріалу до вмісту кортиколіберину і β-ендорфіну, а також коефіцієнт їх вмісту в паравентрикулярному ядрі … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…One of the latest major acquisitions in the field has been the use of transgenic mice with a decreased expression of the rapid vesicular transporter of choline back to the synapses that released it (VAChT) (317,393,506). Animals with different degrees of cholinergic damage can be produced (506).…”
Section: Cholinergic Influences On Fear Learning and Its Extinctionmentioning
confidence: 99%
“…One of the latest major acquisitions in the field has been the use of transgenic mice with a decreased expression of the rapid vesicular transporter of choline back to the synapses that released it (VAChT) (317,393,506). Animals with different degrees of cholinergic damage can be produced (506).…”
Section: Cholinergic Influences On Fear Learning and Its Extinctionmentioning
confidence: 99%
“…The positive effect was maintained for at least 10 days. 10 These findings in preclinical animal studies suggested possible utilization of IHT in control or treatment of type 2 diabetes and its associated insulin resistance. It is notable that the favorable effects of IHT on glucose metabolism were also suggested.…”
Section: Introductionmentioning
confidence: 95%